The Internet of elsewhere : the emergent effects of a wired world - Farivar, Cyrus (Rutgers University Press, 2011)
Through the lens of culture, The Internet of Elsewhere looks at the role of the Internet as a catalyst in transforming communications, politics, and economics. Cyrus Farivar explores the Internet's history and effects in four distinct and, to some, surprising societies-Iran, Estonia, South Korea, and Senegal. He profiles Web pioneers and surveys the environments in which they each work. Farivar contends that despite California's great success in creating the Internet and spawning companies like Apple and Google, in some areas the United States is still years behind other nations.